2018
DOI: 10.1016/j.ebiom.2018.07.009
|View full text |Cite|
|
Sign up to set email alerts
|

Plasma Concentrations of Long Chain N-3 Fatty Acids in Early and Mid-Pregnancy and Risk of Early Preterm Birth

Abstract: Background Fish oil supplementation has been shown to delay spontaneous delivery, but the levels and clinical significance remain uncertain. We examined the association between plasma fatty acids quantified in pregnancy and subsequent risk of early preterm birth. Methods In a case-control design nested in the Danish National Birth Cohort, we identified 376 early preterm cases (<34 gestational weeks, excluding preeclampsia cases) and 348 random controls. Plasma eicosapen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 38 publications
5
78
2
4
Order By: Relevance
“…Early studies showed that low consumption of seafood was a strong risk factor for preterm delivery and LBW [190]. This group also showed that maternal plasma concentrations of EPA and DHA during early and mid-pregnancy were strongly associated with early preterm birth, with lower levels of the lipids leading to higher risk [191]. DHA supplementation during pregnancy resulted in longer gestation duration, fewer preterm births, greater mean birth weight, length and head circumference, significantly fewer infants who were admitted to an intensive care unit, and shorter hospital stays for infants born preterm [192][193][194].…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 98%
“…Early studies showed that low consumption of seafood was a strong risk factor for preterm delivery and LBW [190]. This group also showed that maternal plasma concentrations of EPA and DHA during early and mid-pregnancy were strongly associated with early preterm birth, with lower levels of the lipids leading to higher risk [191]. DHA supplementation during pregnancy resulted in longer gestation duration, fewer preterm births, greater mean birth weight, length and head circumference, significantly fewer infants who were admitted to an intensive care unit, and shorter hospital stays for infants born preterm [192][193][194].…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 98%
“…Clinical effects correlate less well with intake than with blood levels. An example is premature birth before week 34 of pregnancy, which is more likely with low levels than with high levels of EPA and DHA, with risk for preterm birth correlating inversely with levels in erythrocytes, whole blood, or plasma [11][12][13][14]. Data derived from assessments of intake of EPA and DHA showed smaller risks, if at all detected, and no association with dose [15].…”
Section: Intake Vs Blood Levelsmentioning
confidence: 99%
“…EPA und DHA haben sowohl individuelle als auch gemeinsame biologische Aktivitäten, die aber nicht von α-Linolensäure ersetzt werden können; so wird etwa die Endothelfunktion von EPA und DHA, nicht aber von α-Linolensäure gebessert. Hohe Spiegel von EPA und DHA, nicht aber hohe Spiegel von α-Linolensäure sind mit einer geringen Gesamtmortalität und geringen Raten an kardiovaskulären und anderen relevanten Erkrankungen, wie Frühgeburten oder Major-Depression, assoziiert [17,18,21,22,29,37].…”
Section: Fettsäuren -Omega-3-fettsäurenunclassified
“…Niedrige Spiegel von Omega-3-Fettsäuren sind kausal für Frühgeburten [27,29]. Mit Omega-3-Fettsäuren lassen sich die perinatale Mortalität, Frühgeburten und weitere perinatale Komplikationen für Kind und Mutter vermindern [27].…”
Section: » Viele Mütter Verarmen In Und Nach Der Schwangerschaft An Ounclassified